Gross Motor Skills of Grade 7 Learners: Basis for Development of Training Program - Galang, Rogelio (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
This causal-comparative study assessed the gross motor skills of Grade 7 students at Muñoz National High School to guide an intervention program. Using the Test of Gross Motor Development-2 (TGMD-2), data were analyzed via descriptive statistics, the Mann-Whitney U, and Kruskal-Wallis tests. Results revealed that both locomotor (e.g., running, hopping) and object control skills (e.g., catching, dribbling) were below average, with 56.2% of students scoring below the average range; 4.3% were classified as very poor, and 16.3% as poor. Males generally performed better than females, and underweight or normal-weight students displayed higher locomotor skills than heavier peers. Demographic factors like age and socioeconomic status showed no significant impact on motor performance. An intervention program was developed to address these skill gaps, with recommendations for individualized support and a safe learning environment to enhance students' gross motor skills and physical fitness.